3D printing : breakthroughs in research and practice (IGI Global, 2017)
"This book is a comprehensive reference source for the latest research and advances on 3D printing processes, technologies, and methods, highlighting emerging perspectives on manufacturing and industrial applications"--Provided by publisher.
Keywords: Three-dimensional printing.; elektronické knihy; electronic books